2013
DOI: 10.1186/1472-6963-13-502
|View full text |Cite
|
Sign up to set email alerts
|

Assessing responsiveness of health care services within a health insurance scheme in Nigeria: users’ perspectives

Abstract: BackgroundResponsiveness of health care services in low and middle income countries has been given little attention. Despite being introduced over a decade ago in many developing countries, national health insurance schemes have yet to be evaluated in terms of responsiveness of health care services. Although this responsiveness has been evaluated in many developed countries, it has rarely been done in developing countries. The concept of responsiveness is multi-dimensional and can be measured across various do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

33
108
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(148 citation statements)
references
References 21 publications
33
108
7
Order By: Relevance
“…With respect to health care funding, Nigeria government does not yet operate a full universal healthcare coverage. Conversely, out of pocket payment by patients is predominating while the national health insurance scheme that is in operation is predominantly targeted at Nigerian population employed in the formal sector of the economy [56]. Therefore, the present healthcare funding arrangement in placed may robbed appreciable segment of population of ease of access to desire healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to health care funding, Nigeria government does not yet operate a full universal healthcare coverage. Conversely, out of pocket payment by patients is predominating while the national health insurance scheme that is in operation is predominantly targeted at Nigerian population employed in the formal sector of the economy [56]. Therefore, the present healthcare funding arrangement in placed may robbed appreciable segment of population of ease of access to desire healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…It is a crucial aspect in the professional-user relation that fosters questioning about therapy and the disease. (10) Communication between professionals and users has also been satisfactorily evaluated in this study. Communication should break the barrier of information asymmetry, building new possibilities of understanding and solving the problems perceived.…”
Section: Discussionmentioning
confidence: 87%
“…However, the domains of autonomy, communication, and prompt care were identified as priority areas of action to improve the system's capacity of response. (10) Regarding the users' profiles, it was found that health services, notably the FHS, were more sought after by women, showing their concern about taking care of their health. Other reasons for increased adherence to and use of health services by women can be explained by the physiology and life cycles of women, which demand regular care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations